Pembelajaran Matematika pada Faktor Persekutuan Terbesar dan Kelipatan Persekutuan Terkecil di Sekolah Dasar - Andriani, Anita; Al Ayyubi, Ibnu Imam; Nurhikmah; Prayetno, Eko; Khan, Anis (Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the impact of mathematics learning on the concepts of the Greatest Common Divisor (GCD) and the Least Common Multiple (LCM) on students' abilities at SDN Pasir Banteng, West Bandung Regency. The population consisted of all students at SDN Pasir Banteng, with a sample of 40 fifth-grade students. The research employed a quantitative method with an explanatory research approach and a causal-correlational study design. The sampling technique used was probability sampling with simple random sampling, and the instruments included questionnaires and tests that had been validated and tested for reliability. Validity and reliability tests were conducted by comparing Cronbach’s Alpha with Cronbach’s Alpha if Item Deleted, using SPSS version 26. The normality test using the Kolmogorov-Smirnov method indicated that the data were not normally distributed, with significance values of 0.000 and 0.003 (p < 0.05). This was also supported by the analysis of the Normal Q-Q Plot, where the data points were not clustered around the diagonal line. Consequently, a non-parametric statistical analysis using Spearman’s correlation was conducted. The results showed a significance value of 0.002 (p < 0.05), indicating a significant impact of GCD learning on students' abilities to understand LCM. The Correlation Coefficient value of 0.470 demonstrated a moderate relationship between the two variables. Therefore, it can be concluded that GCD learning has a significant correlation with students' understanding of LCM, emphasizing the need for teachers to integrate these two concepts effectively in the learning process.